Mitos sebagai Narasi dalam Iklan Rokok Gudang Garam: Analisis Semiotika Roland Barthes - Taqdir, Taqdir; Masdiana, Masdiana; Nursakinah, Nursakinah; Muhammad, Hasyim (Faculty of Humanities, Diponegoro University, 2025)
This article examines how Gudang Garam Filter International advertisements construct myths of masculinity, power, and success using visual and narrative elements. Using Roland Barthes’s semiotic approach, which conceptualizes myth not as falsehood but as a culturally constructed narrative that gives ideological meaning to signs, this study analyzes symbols such as dark colors, luxury cars, formal clothing, and dominant activities that create the image of a strong and sophisticated man. The analysis shows that these elements build a narrative of a successful man who dominates his social environment despite contradicting government health warnings. Ethical implications are also discussed considering how such advertisements may create cognitive dissonance among consumers. Furthermore, although consumers are generally aware of the dangers of smoking, factors such as addiction, identity seeking among teenagers, and the tobacco industry's contribution to the national economy highlight the complexity of the issue. This study emphasizes the need for critical awareness in interpreting advertising narratives in broader social and public health realities.